In vitro infection of primary human hepatocytes by HCV-positive sera: insights on a highly relevant model. Issue 9 (23rd October 2013) - Gondeau, Claire; Briolotti, Philippe; Razafy, Francia; Duret, Cédric; Rubbo, Pierre-Alain; Helle, François; Rème, Thierry; Ripault, Marie-Pierre; Ducos, Jacques; Fabre, Jean-Michel; Ramos, Jeanne; Pécheur, Eve-Isabelle; et al.
Abstract : Objective: Adult primary human hepatocytes (PHHs) support the complete infection cycle of natural HCV from patients' sera. The molecular details underlying sera infectivity towards these cells remain largely unknown. Therefore, we sought to gain a deeper comprehension of these features in the most physiologically relevant culture system. Design: Using kinetic experiments, we defined the optimal conditions to infect PHH and explored the link between cell organisation and permissivity. Based on their infectivity, about 120 sera were classified in three groups. Concentration of 52 analytes was measured in 79 selected sera using multiplexed immunobead-based analyte profiling. Results: PHH permissivity towards HCV infection negatively correlated with cell polarisation and formation of functional bile canaliculi. PHH supported HCV replication for at least 2 weeks with de novo virus production. Depending on their reactivity, sera could be classified in three groups of high, intermediate or low infectivity toward PHH. Infectivity could not be predicted based on the donors' clinical characteristics, viral load or genotype. Interestingly, highly infectious sera displayed a specific cytokine profile with low levels of most of the 52 tested analytes. Among them, 24 cytokines/growth factors could impact hepatocyte biology and infection efficiency. Conclusions: We identified critical factors leading to efficient PHH infection by HCV sera in vitro. Overall, we showed that this cellular model provides a useful tool for studying the mechanism of HCV infection in its natural host cell, selecting highly infectious isolates, and determining the potency of drugs towards various HCV strains.